Answer to Question #14863 in Trigonometry for geethanjali
Prove that: sin4A-cos4A=sin2A-cos2A
1
2012-09-14T12:09:41-0400
This statement is wrong. Let's take A = π/12, for example:
sin4A-cos4A = sin4(π/12)-cos4(π/12) = sin(π/3) - cos(π/3) = √3/2 - 1/2.
But
sin2A-cos2A = sin2(π/12)-cos2(π/12) = sin(π/6)-cos(π/6) = 0.5 - √3/2
and
& radic;3/2 - 1/2 ≠ 0.5 - √3/2.
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment